Integrating Artificial Intelligence to Enhance Students’ English Writing Competence: Evidence from a Quasi-Experimental Study - Fibri Indira Lisanty AD; Andi Mangnguntungi Sudirman; Nur Ummul Khaerat (Faculty of Education and Teacher Training of UIN Palopo, 2025)
This research investigates the influence of artificial intelligence (AI) as an interactive learning medium in enhancing students’ English writing skill, with a particular focus on midwifery students at the Pelamonia Institute of Health Sciences. Writing skill is a crucial skill in academic and professional contexts; however, many students face challenges related to grammar, vocabulary, and coherent text organization. To investigate the influence of Artificial Intelligence as interactive learning medium in enhancing students’ writing skill, the researcher employed a quasi-experimental design. It was employed with two groups: an experimental group using AI-based learning media and a control group applying conventional methods. Data were collected through pre-tests, post-tests, questionnaires, and classroom observations. The results reveal that there is a significant influence in the experimental group after implying AI as the medium in writing learning. It is proven by the result of two-way ANOVA analysis confirmed a statistically significant difference between the groups (p < 0.05). In addition to cognitive gains, the integration of AI supported students’ metacognitive development by enabling self-evaluation, independent learning, and strategic awareness during the writing process. Questionnaire findings further indicate that students perceived AI as an effective, motivating, and user-friendly tool, although challenges such as limited technological access and potential overreliance were identified. Overall, the findings concludes that AI integration is highly influence in enhancing English writing skill, offering pedagogical implications for technology-enhanced language learning.